Finnish Theatre Photography and the Influence of Technology - Virkki, Susanna (Nordic Theatre Studies, 2014)
This article is mainly based on interviews with three Finnish photographers’, Kari Hakli, Jalo Porkkala, and Petri Nuutinen’s as well as on the theatre photographs they have taken. The criterion for selecting these three photographers has been that their work spans a number of decades; therefore, the development of Finnish theatre photography can be studied from this perspective. The theatre photograph is a photo of the stage image, which is often based on the dramaturgy of the play script. The subjects and points of view of the photographer are not generally agreed on in advance with the director or the actors, but they are based on the photographer’s own estimations and views. He/she interprets and transmits the performance to the audience with his images, and works in between the theatre and the spectator, but he is not the artistic producer when photograph- ing, the performance is, i.e. he/she has not chosen lights, costumes or set design. Technology has had a significant influence on the theatrical image and pho- tographic equipment. With the development of materials and equipment, the making of theatre photographs has shifted from a static process into a more dynamic one. Finnish theatre photography has reacted quickly to aesthetic trends in both theatre and photography. In the past it was possible to photograph only static or slow-moving objects in a set situation or in a pose. Today, the photographer can move among the actors, photograph fast-moving objects with a handheld camera using the stage lighting without the need for additional lights. The images look more as if they have been taken by an insider, someone who belongs to the team, rather than by an intruder. Theatre photographs are nowadays needed in the same way they have always been needed, as documents of the performance.